2017
DOI: 10.1007/s00205-017-1192-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Micropatterns in 2D Transport Networks and Their Relation to Image Inpainting

Abstract: We consider two different variational models of transport networks, the so-called branched transport problem and the urban planning problem. Based on a novel relation to Mumford-Shah image inpainting and techniques developed in that field, we show for a two-dimensional situation that both highly non-convex network optimization tasks can be transformed into a convex variational problem, which may be very useful from analytical and numerical perspectives.As applications of the convex formulation, we use it to pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Taking the limit j → ∞ the same holds with d 1 instead of d 1,j , and by continuity of u we obtain (9).…”
Section: Proofmentioning
confidence: 92%
See 1 more Smart Citation
“…Taking the limit j → ∞ the same holds with d 1 instead of d 1,j , and by continuity of u we obtain (9).…”
Section: Proofmentioning
confidence: 92%
“…These vectorial generalizations have confirmed that the Kohn-Müller scalar model indeed captures the correct scaling of the energy. A number of other problems have then been addressed with similar tools, including magnetization patterns in uniaxial ferromagnets [14,15,37], diblock copolymers [1,13], flux tubes in type-I superconductors [16,20,22,28], wrinkling in thin elastic films [4,6,7,34], dislocation microstructures [18,19], transport network structures [8,9], and compliance minimization [42].…”
Section: Introductionmentioning
confidence: 99%
“…The (inexact) proximum may be computed in a straightforward fashion using Dykstra's algorithm [29], which has e.g. been done in [11] or [1,17,Ex. 7.7] for Mumford-Shah-type segmentation problems.…”
Section: Lemmamentioning
confidence: 99%
“…Explicit optima are known only in few (mainly discrete) cases; for this reason, some effort has been put in developing numerical strategies to compute minimizers, for instance in term of phasefield approximations [37,12,4], in the spirit of numerical calibrations [35,3], or exploiting the convex nature of different formulations of some aspects of the problem (which is overall highly nonconvex) [30,31,6].…”
Section: Remark (H-masses)mentioning
confidence: 99%